Solidaritas Sosial Antarumat Beragama (Studi Kasus Pada RW 1 dan RW 2 Kelurahan Babatan Kota Surabaya) - Afelia, Rega Yeni; Muhammad Turhan Yani (Universitas Negeri Surabaya (Unesa), 2024)
This study was written with the aim of describing the mechanism of social solidarity between religious communities that occurs in the RW I and RW II communities of Babatan Village, Surabaya or known as Babatan village. Social solidarity between them is well established even though the society has religious differences. This research method uses a qualitative approach with a case study research design. Informants were selected using the purposive sampling technique. Data collection techniques through observation, interviews, and documentation. Data analysis of the Miles and Huberman model was used in this study. The theory used is Emile Durkheim's theory of social solidarity. The results of the study show that the mechanism of social solidarity in the multi-religious community in Babatan village is divided into three stages. The first stage began with the awareness of the people of Babatan village about the religious differences that exist between them. The second stage, awareness of existing religious differences makes them vigilant to prevent friction, especially conflicts that may occur. Departing from the experience of the people of Babatan village before, there has been a small friction between religious people between them. Therefore, the community seeks to develop tolerance to prevent these things. The third stage, the impact of the process in developing tolerance, it is necessary to build a tool to integrate the community in Babatan village, namely with the ownership of ancestors with Babatan village, the tradition of earth almsgiving, the symbol of Babatan village, and the slogan of Babatan village. The people of Babatan village in the process of developing their tolerance have given rise to social solidarity with the type of organic solidarity.